2021
DOI: 10.34067/kid.0006902020
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing Application for Genetic Diagnosis of Kidney Diseases: A Study from Southwest of Iran

Abstract: This is an Early Access article. Please select the PDF button, above, to view it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In a study with kidney disease patients, pathogenic variants in 68% of patients were identified through wholeexome sequencing. This study demonstrates that whole-exome sequencing holds potential as an emerging diagnostic tool for inherited renal cystic diseases [12].…”
Section: Presentation and Diagnosismentioning
confidence: 75%
“…In a study with kidney disease patients, pathogenic variants in 68% of patients were identified through wholeexome sequencing. This study demonstrates that whole-exome sequencing holds potential as an emerging diagnostic tool for inherited renal cystic diseases [12].…”
Section: Presentation and Diagnosismentioning
confidence: 75%